Consumer's Intentions Towards E-Wallets in the Philippines: A Systematic Literature Review - Shekina Rejean Bacamante; Karl Campos (Journal of International Business, Economics and Entrepreneurship)
Technology advancements and the internet's growth have contributed to the era of a cashless economy via electronic wallets (e-wallets). Several factors influence the usage of these electronic wallets. The main objective of this study is to review the increasing number of studies on consumers' intention to use e-wallets. A Systematic Literature Review (SLR) was employed, and works of literature were prepared using the Funneling Method. 110 articles were filtered, but only 15 were reviewed after screening using the criteria made by the researcher. This method is used to narrow down articles step-by-step and examine research data. Results showed that the most often mentioned factors influencing users' intentions to use e-wallets were security, perceived ease of use, trustworthiness, and usefulness. The most significant one was security, indicating how important it is for users to have confidence in the security of their transactions.